Le Viêt Nam a cessé d'être Protectorat Français - France Illustration... - The New York Times. (Wikimedia Commons, 1950)
Notice iconographique issue de Wikimedia Commons. Titre: Le Viêt Nam a cessé d'être Protectorat Français - France Illustration (Le Monde Illustré) 1950. The official proclamation of the end of the French protectorates over Vietnam showing Emperor Bo Đi and the government of the State of Vietnam signing the agreement ending the protectorates over Annam and Tonkin.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie